VIKET, Framing views - Lundahl,Thea (2025)
This thesis project explores the relationship between architecture and nature, with a focus on framing views, capturing the landscape and engaging with our senses. The main building consists of a sensory sauna that allows visitors to feel connected to the surrounding nature while being sheltered from the harsh climate.